XUV pump-probe experiments on diatomic molecules : tracing the dynamics of electron rearrangement and interatomic coulombic decay /: tracing the dynamics of electron rearrangement and interatomic coulombic decay. (2015) - Schnorr, Kirsten
No abstract available